Anti-inflammatory treatment strategies for ischemia/reperfusion injury in transplantation - Heemann Uwe; Thürmel Klaus; Lutz Jens (BMC, 2010)
Abstract Inflammatory reactions in the graft have a pivotal influence on acute as well as long-term graft function. The main reasons for an inflammatory reaction of the graft tissue are rejection episodes, infections as well as ischemia/reperfusion (I/R) injury. The latter is of particular interest as it affects every solid organ during the process of transplantation. I/R injury impairs acute as well as long-term graft function and is associated with an increased number of acute rejection episodes that again affect long-term graft outcome. I/R injury is the result of ATP depletion during prolonged hypoxia. Further tissue damage results from the reperfusion of the tissue after the ischemic insult. Adaptive cellular responses activate the innate immune system with its Toll-like receptors and the complement system as well as the adaptive immune system. This results in a profound inflammatory tissue reaction with immune cells infiltrating the tissue. The damage is mediated by various cytokines, chemokines, adhesion molecules, and compounds of the extracellular matrix. The expression of these factors is regulated by specific transcription factors with NF-κB being one of the key modulators of inflammation. Strategies to prevent or treat I/R injury include blockade of cytokines/chemokines, adhesion molecules, NF-κB, specific MAP kinases, metalloproteinases, induction of protective genes, and modulation of the innate immune system. Furthermore, preconditioning of the donor is an area of intense research. Here pharmacological treatment as well as new additives to conventional cold storage solutions have been analyzed together with new techniques for the perfusion of grafts, or methods of normothermic storage that would avoid the problem of cold damage and graft ischemia. However, the number of clinical trials in the field of I/R injury is limited as compared to the large body of experimental knowledge that accumulated during recent years in the field of I/R injury. Future activities in the treatment of I/R injury should focus on the translation of experimental protocols into clinical trials in order to reduce I/R injury and, thus, improve short- as well as long-term graft outcome.